Simulasi Monte Carlo dan Penerapannya dalam Menentukan Probabilitas Pergerakan Saham Indeks LQ-45 - Anastasia, Vira; Subhan, Muhammad (UNIVERSITAS NEGERI PADANG, 2022)
The problem for investors when investing is determine stocks that have the opportunity to move up that they get maximum profits in the future. The purpose of this study is to determine the opportunities for movement of the LQ-45 index stock. This study uses data on closing prices for daily stocks listed the LQ-45 index in the period February 2021-January 2022. To find out the opportunities for stock movements, a monte carlo simulation is used which based on the stock price movement model, the stock price movement model is influenced by the latest stock price and brown geometry motion 100 times and 10000 times simulation for 10 days of stock trading. Based on the results of the simulation analysis, the average share price was Rp. 916 - Rp. 23000, the value of forecasting accuracy namely very good forecasting accuracy with an average error of less than 10%. Companies that have increased opportunities for 10 trading days in February 2022 are CPIN.JK, INCO.JK, INKP.JK, and TBIG.JK.